(untitled) (MAUSAM, 1960)
Group or storm type microseisms were recorded during the passage of Nor’westers over the head Bay of Bengal. These microseisms are of frontal type and in the present paper they have been ascribed to cold fronts associated with the Nor’westers. No direct methods based on meteorological observations could be successfully used to prove the existence of the cold fronts associated with Nor’westers during pre-monsoon season. It is considered that microseisms furnish indirect evidence about the existence of the cold fronts in Nor’westers.